Potensi Antagonistik Bakteri Lactobacillus plantarum terhadap Bakteri Patogen Aeromonas salmonicida Secara In Vitro [The Potential Antagonistic Bacterium Lactobacillus plantarum Against Bacterial Pathogens Aeromonas salmonicida By In Vitro] - Gunanti Mahasri; Yunifar Amad; Rahayu Kusdarwati (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Problems were often experienced by fish farmers is bacterial pathogen Aeromonas salmonicida which causes furunculosis disease in fish. The way to control the growth of this pathogenic bacteria was using antagonist bacteria of Lactobacillus plantarum. Growth of L. plantarum may inhibit contamination of pathogenic bacterial because of its ability to produce bacteriocins, produce lactic, moreover that these bacteria can produce hydrogen peroxide which can function as an antibacterial. This research aimed to provide information on the use of bacterial antagonists L. plantarum in inhibiting the growth of pathogenic bacteria A. salmonicida on In Vitro. This research was conducted on October 2012 until January 2013 at dry laboratory in Fisheries and Marine Faculty of Airlangga University Surabaya. This research used Completely Randomized Design (CRD) with five treatments and four replications. Bacteria L. plantarum with 0 concentration for control (A), 106 (B), 107 (C), 108 (D), 109 (E) tested challenge by paper disc method with 106 concentrate of pathogenic bacteria A. salmonicida in vitro. The results showed that L. plantarum with a concentration of 109 CFU/ml (E) was a treatment that produced average of obstacle on the distribution of A. salmonicida amounted to 12,375 mm. Then the treatment with a concentration of 108 CFU/ml (D) with the average of obstacle 8,95 mm. While treatment with a concentration of 107 CFU/ml (C) and 106 CFU/ml (B) was having average of obstacle 6.8 mm and 6 mm was not significantly different from the control (A) which had an average 6 mm obstacle. So it could be concluded that bacteria L. plantarum had antagonistic potential against bacterial pathogens A.salmonicida which indicated by the obstacle produced by L. plantarum on growth of pathogenic bacteria A.salmonicida.